Memorias de familia (2020)
Family memory is built from events, objects and images that families collect over the years and are passed from generation to generation. These relics and stories convey an imprint that gives families a sense of belonging. The process of creating this work is motivated by my personal interest in the memory of my family and a need to explore and rethink it in a work that is based on the virtual nature of images and their fragile existence. I feel that the images of our memories and also those that are saved on external media such as photography or video, have a fragile nature and I wanted to express this feeling. I have thought during this process that the matter of memory is soluble and becomes liquid and malleable. It transforms and has the potential to change and rebuild. This work becomes a reflection on the memory that I wanted to keep from my relatives but also on how I appropriated these traces and reflected on their virtuality. It became a small memorial to their lives from the personal selection of some objects and images that became the main motifs of the work.